2009
DOI: 10.1292/jvms.71.745
|View full text |Cite
|
Sign up to set email alerts
|

Histoplanimetrical Study on the Relationship between Cellular Kinetics of Epithelial Cells and Proliferation of Indigenous Bacteria in the Rat Colon

Abstract: ABSTRACT. The aim of this study was to clarify the regulatory effects of epithelial kinetics on indigenous bacterial proliferation in the large intestine. The lifespan, migration speed and proliferation rate of crypt epithelial cells in the initial 20% of the colon (proximal colon) and the 50% of the colon (middle colon) in bromodeoxyuridine-administrated rats were histoplanimetrically and chronologically compared. The proximal colon possessed well-developed mucosal folds and a large amount of indigenous bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In the rat ascending colon, numerous indigenous bacteria settle between the mucosal folds [27]. In the present study, white substances which were macroscopically found between the mucosal folds were microscopically confirmed to be the accumulations of almost all bacteria.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the rat ascending colon, numerous indigenous bacteria settle between the mucosal folds [27]. In the present study, white substances which were macroscopically found between the mucosal folds were microscopically confirmed to be the accumulations of almost all bacteria.…”
Section: Discussionsupporting
confidence: 74%
“…From these findings, stable bacterial settlement is speculated to be maintained by the balance between the bacterial proliferation and the elimination of bacteria by host defense in the rat small intestine. On the other hand, the deceleration of epithelial cell migration might contribute to the reliable settlement of indigenous bacteria in the basal part of the mucosal folds in the rat ascending colon [27]. However, it has not been fully clarified how bacterial invasion into the intestinal crypts effects the epithelial cell kinetics in the rat ascending colon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These portions are also epithelial cell-shedding sites and accumulation sites of epithelial cells in the late-apoptotic stage in rats [30,33,34]. These accumulation sites of epithelial cells in the lateapoptotic stage also absorb the luminal food-derived antigens and their antibody complexes in the rat small intestine [43,44].…”
mentioning
confidence: 94%
“…The lifespan and migration speed of columnar epithelial cells are crucial factors in the regulation of the settlement of indigenous bacteria in the rat small and large intestine. Therefore, the stable settlement of indigenous bacteria is considered to be maintained by the delicate balance of the proliferation rate of indigenous bacteria over the exfoliation rate of effete apoptotic epithelial cells [20,21]. In addition, the indigenous bacteria closely attached to the epithelial cell membranes are eliminated by physical and chemical elimination by epithelial cells themselves [10,11].…”
mentioning
confidence: 99%